Systematic Literature Review Keberlanjutan Implementasi Green Investment Perbankan Di Indonesia Dengan Pendekatan Bibliometrik Berbasis Prisma - Andrea Chandra; Febriyanti G. Hunga; Ade Try Pratama; Sesilia Wilgis Klau; Rolland Epafras Fanggidae; Yonas Ferdinand Riwu (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
The banking sector plays a strategic role in supporting sustainable development through green investment. However, research on the sustainability of green investment implementation in Indonesia’s banking sector remains limited. This study aims to analyze research developments from 2019 to 2025 by identifying research themes, topic interrelationships, and the challenges and opportunities associated with implementation. This study employs a Systematic Literature Review method with a bibliometric approach based on PRISMA. Articles were obtained from Google Scholar and selected from SINTA accredited journals and relevant Q1–Q4 international journals. The findings indicate that research on green investment in Indonesia’s banking sector remains limited and has not specifically focused on sustainability issues. Major challenges include emphasis on short-term investment returns, regulatory inconsistencies, greenwashing risks, limited human resource capacity, and low investor confidence. Nevertheless, opportunities for sustainable implementation are supported by green accounting, banking digitalization, green sukuk development, and integration with the blue economy concept. This study is expected to provide a reference for future research, policy development, and academic discussion in promoting sustainable green investment in Indonesia’s banking sector.